Topological Variations of the Inverse Dual Converter for High Power DC-DC Applications - Ehsani, M.; Laskai, L.; Bilgiç, Mehmet Oruç (IEEE, 1990)
DC to DC power converter topologies that are suitable for high-density, high-power supplies are presented. Topological variations on the basic inverse dual converter (IDC) circuit, such as the coupled transformer and the multiphase and multipulse derivation of the single-phase IDC, are analyzed, and simulation results are discussed. The topologies have most of the IDC features, such as buck-boost operation, bidirectional power processing, capacitive commutation for switches, and unlimited high-power capability. The multiphase, the coupled transformer, and the power distribution IDC topologies offer additional properties, such as significant power-density improvement isolation. AC tapping, and input-current reduction. A quantitative comparison between the single- and the multiphase IDC is presented.
Keywords: DC-DC power converters; Pulse width modulation; Resonance; Bridge circuits; Switches; Frequency; Stress; DC motors; Circuit topology; Bidirectional power flow